LIGHT: Leadership for social impact - Zakariya, Khalilah; Awang, Muhammad Nizam; Tumian, Afidalina; Mohyin, Nur Affah; Shamsul Harumain, Zakuan Azizi (2019)
LIGHT is a leadership enrichment initiative programme for university students collaboratively organised by two universities in Malaysia and an industry partner, which are International Islamic University Malaysia (IIUM), Universiti Sains Islam Malaysia (USIM) and Permodalan Nasional Berhad (PNB). Realising the needs to continuously strengthen the tripartite relationship between academia, industry and the community, LIGHT was proposed with the aim to expose students to their roles as members of the society by creating opportunities for them to hone their self-development, teamwork, leadership, social responsibility, and sharpening their problem-solving skills. LIGHT is an acronym that represents five values of leadership aimed to be imparted through this programme, which are: Leadership, Intuitive, Giving, Humility and Tenacity. These values are parallel to the National Education Philosophy in developing a balanced and harmonious individual. As a programme that emphasises on leadership for social impact, LIGHT will be conducted through a project-based approach in regenerating cultural products of the Gombak community. The conference presentation will share the activities of LIGHT and processes involved, which range from exploring the potentials of the community products to planning for their growth and sustainability for the future, while enhancing the role of university for society.